Integrating Online Corpus and Online Dictionary to Expand Student's English Vocabulary for Tourism - andi rizki fauzi; s suradi (Indonesian Journal of Integrated English Language Teaching, 2019)
This study was aimed to know the contribution of online corpus integrated with an online dictionary to take part in learning English vocabulary for tourism. An experimental research was conducted toward the fourth semester of Diploma III students at STIPARY Tourism Academy majoring in Hospitality. The population consists of 118 students and they were divided into 4 classes in which class A and B were randomly chosen as the samples. 100 words from the corpus created from articles in the tourism field were listed through the corpus data and the level of familiarity rated by the students. Based on the analysis result, it could be seen that Asymp. Sig (2-tailed) value was 0,000, which was less than the probability value of 0,05. It means that integrating online corpus and online dictionary could be significantly expand the students' English Vocabulary for tourism.